Study The Readiness Of E-Learning Mode In Iran - Pouryazdanpanah, Maryam (2009)
This study attempts to discuss readiness of Iranian universities towards e-learning. This study also siscuss the obstacles in the path of both developing e-learning in Iranian universities and the willingness and the ability of Iranian students towards learning through e-learning mode.